On the inhomogeneous deformation behavior of magnesium alloy beam subjected to bending. (March 2022) - Tang, Ding; Zhou, Kecheng; Tang, Weiqin; Wu, Peidong; Wang, Huamiao
Highlights: A crystal plasticity-based approach is developed for the bending behavior of magnesium alloy. The approach captures both macro- and micro- mechanical behaviors of magnesium alloys subjected to bending. The proposed approach can be used to tailor gradient twin structure that is potential to achieve superior mechanical properties. The proposed approach can collaborate easily with sophistical constitutive models and has superior computational efficiency. Abstract: Magnesium (Mg) alloys have attracted worldwide attention as potential lightweight structural materials. However, it is still a big challenge to manufacture or process Mg alloys that have good formability and endure high strength. This mainly stems from the lack of understanding the anisotropic mechanical behavior of Mg alloys subjected to inhomogeneous deformation which exists inevitably in various material processing routes. In this respect, the current work seeks to explore and understand the bending behavior of Mg alloy. Mechanical response and microstructure development were experimentally characterized by performing four-point bending tests, with the use of the in-situ digital-image-correlation (DIC) and ex-situ electro backscattered diffraction (EBSD) measurements. Meanwhile, a crystal plasticity-based approach was proposed and used to illustrate the characteristic deformation behavior under four-point bending. The inhomogeneous and anisotropic nature of the mechanical response of Mg alloys under bending is successfully captured by the proposed approach in terms of the moment-curvature relation, the deformed cross-sectional shape of the beam, the developed textures at different regions of the beam, the spatial distribution of the stress and strain components, and the twin volume fraction. The insight of the slip/twinning mechanisms underlying the bending behavior of Mg alloy beam offers a novel way for designing/tuning gradient twinning structures that might lead to the optimized properties of Mg alloys.